Controlling intraoperative laparoscopy-induced pneumothorax using a novel technique - Alqahtani, Awadh; Almayouf, Mohammad; Billa, Srikar (International Surgery Journal, 2022)
Pneumothorax (PTX) is defined as an abnormal accumulation of gas in the pleural space. There is a potential development of PTX during laparoscopy since gas insufflation is used. Management options are available to control PTX intraoperatively, and herein we describe a new technique that can be implemented with unique features. A 32-year-old patient with morbid obesity was scheduled for laparoscopic adjustable gastric band (AGB) removal and laparoscopic sleeve gastrectomy (LSG). During the removal of AGB, a hiatal hernia was noticed. Dissection of the hernia led to PTX. Images were collected from the procedure video to describe our technique in controlling laparoscopy-induced PTX. Upon noticing PTX, actions were taken promptly using our technique. The anesthesia team was alerted, the abdomen was deflated, and the table was positioned to Trendelenburg. The PTX was controlled using a 14fr feeding tube advanced through the dissected esophageal hiatus, with the external end submerged under saline. The procedure was completed with no complications. Our technique in controlling laparoscopy-induced PTX is effective in certain situations. The technique assures completing the procedure without hindrance with minimal morbidity.